Efeito amnésico da arcaína depende da novidade e do sistema opióide - Rosa, Michelle Melgarejo da (2012)
Previous exposure to the training context disrupts glutamatergic N-methyl-Daspartate receptor (NMDAr) antagonist-induced amnesia, indicating that novelty is necessary for such an amnestic effect. While there are reports that novelty-related release of opioids cause amnesia, no study has addressed whether the amnestic effect of NMDAr antagonists involve opioid mechanisms. In this study we investigated whether pharmacological manipulation of the opioid system immediately after context pre-exposure alters the amnestic effect of arcaine, a NMDAr antagonist. Adult male Wistar rats were habituated (pre-exposed) to a fear conditioning training apparatus or to a different context (open field). Immediately after pre-exposure, animals were injected with saline or naloxone (0.5 mg/kg, i.p.) or anti-beta-endorphin antibody (1:500, i.c.v.). Forty eight hours after pre-exposure session, all animals were subjected to fear conditioning acquisition protocol and saline or arcaine (30 mg/kg, i.p.) was administered immediately after training. Testing was carried out 24 h later, and freezing responses due to re-exposure to the training apparatus were recorded. Pre-exposure to the training apparatus prevented the impairment of memory induced by post-training arcaine. Administration of naloxone or anti-beta-endorphin antibody, immediately after pre-exposure to the training apparatus, reinstated the amnesic effect of post-training arcaine. The results suggest that endogenous opioid mechanisms are involved in the pre-exposure-induced loss of the amnestic effect of arcaine.